Analisis Pengaruh Keadilan Pajak, Kesederhanaan Pajak dan Pengetahuan Pajak Terhadap Kepatuhan Pajak Pelaku UMKM - Nainggolan, Junsun; Inayati (Politeknik Ganesha Medan, 2024)
The primary source of revenue for a country primarily comes from tax receipts. One of the key supports for tax revenue is the tax payments made by micro, small, and medium-sized enterprises (MSMEs). Only now, the tax payments made by MSMEs have been perceived as not contributing maximally to the state's revenue. The government has made efforts to enhance tax revenue by providing tax facilities, aiming to promote fairness and simplify tax administration for taxpayers, with the hope of achieving a sense of justice and administrative efficiency in tax compliance, which is expected to increase the willingness of taxpayers to fulfill their tax obligations. This research is conducted to determine the influence of tax fairness, tax simplicity, and tax knowledge possessed by MSME taxpayers on their compliance with tax obligations based on tax regulations. The independent variables in this study are tax fairness, tax simplicity, and tax knowledge, while tax compliance by MSME taxpayers is tested as the dependent variable. The population in this research includes 50 samples of individual MSME taxpayers in the Kramatwatu District, Serang Regency, Banten. The data collected is processed using the SPSS program with multiple linear regression analysis. The results obtained from this research show that tax fairness and tax simplicity have a significant impact on the tax compliance of individual MSME taxpayers in the Kramatwatu District, Serang Regency. In contrast, tax knowledge does not have a significant influence.